A LABORATORY STUDY OF LIME - SOIL COLUMNS IN BANDUNG CLAY - Hamonangan Simanjuntak, Armas
This thesis describes an investigation, at laboratory scale, into the possible use of lime-soil columns in Bandung clay, as a means of improving the settlement response under load of this highly compressible ground. Consolidation tests were performed on natural soil, natural , soil combined with lime and natural soil containing a lime-soil column. Consolidation characteristics of natural soil combined with lime and natural soil containing a lime-soil column were determined after the specimens had been cured for 2 days at 50Â°C. The crustal, semi-crustal and main soft samples were separated to obtain a clearer trend. Samples were tested with lime contents of 3, 6, 9, 12, and 15 per cent by the dry weight of soil. This range was chosen, based on experience elsewhere, to determine the effective lime content. Analysis of consolidation test results shows that the consolidation settlement is reduced by the addition of lime content and the effect increases as a function of lime content and lime-soil column diameter. Furthermore an increase in lime content increases the rate of consolidation for this soil .